The Relationship of Social Support and Religious Orientation with Relapse Rates in Opioid Dependent Patients under Methadone Maintenance Therapy - Ashrafi Hafez, asghar; Kazemeini, toktam; Shayan, shadi (Advances in Nursing & Midwifery, 2015)
Abstract Background and Aim: Dependency to opium is a chronic and relapsing disorder that imposes great costs on individuals, families and society. The aim of this study is examining the relation between social support and religious orientation with relapse rates in opioid dependent patients under methadone maintenance therapy. Materials and Method: A descriptive –correlational design was used. The sample of the study consisted of a convenience sample of 200 male patients , were referred to substance treatment clinics of Mashhad since March 2012 to August 2012 and were treated by methadon. Sample was evaluated with Social Support Scale, Allport’s Religious Orientation questionnaire and demographic information form. Data were analyzed with Pearson correlation coefficient, enter and stepwise multiple regression. Results: The results of this study revealed internal religious orientation (r=-0.52), family support (r=-0.48), and friends’ support (r=-0.33) were all in significant negative correlation with relapse rates (p< 0.01). It means that by increasing family support and internal religious orientation,the relapse rates were decreased. Also there was a significant positive correlation between external religious orientation and relapse rates (r=0.50, p<0.01). Findings of linear regression and hierarchical regression analysis showed that all of these variables are predicting in total 0.62 of relapse rates variance, from which the contribution of internal religious orientation, external religious orientation, and family support respectively was 0.27, 0.06 and 0.04. Conclusion: results showed increasing of internal religious orientation and family support is associated with decreasing in relapse rates, and increasing of external religious orientation is associated with increasing in relapse rates. Keywords: methadone maintenance therapy, opioid dependent patients, relapse rates, religious orientation, social support. REFERENCES Agha Delavarpoor M, Soltani M, Hosseinchari M (2008) [Prediction of Recovery or Relapse from Substance Abuse, Based on the Emotional Intelligence and Religious Coping]. Iranian Journal of Psychiatry and Clinical Psychology .14 (3) 307-315. (Persian) Amey CH, Albrecht SL, Miller MK (1996). Racial differences in adolescent drug use: The impact of religion. Subst Use Misuse. 31 (10).1311-1332. Amini K, Amini D, Afshar-Moqadam F, Azar M (2003) [Examining social and environmental factors related to relapse of addicts to miuse of opium in clients to public center of addiction rehabilitation in Hamedan city]. Zanjan University of Medical Sciences . 45 (10). 41-47. (Persian) Amirpoor L, Alavi Kh (2010) [The relationship of Perceived social support with level of anxiety in university students]. The fifth seminar of college student’s mental health . Tehran, Iran. (Persian) Bakhshipoor Rodsari A, Peyravi H, Abedian A (2005) [Examinig the relationship of life satisfaction and social support with mental health in university students]. journal fundamental mental health Mashhad University of Medical sciences .7 (27, 28) 145-152. (Persian) Beck AT, Right FD, Newman K, Lys BS (2001). Cognitive therapy of substance abuse . Translated by Godarzi MA. Shiraz, Iran. Rahgosha publicaton. Besharat MA, Ranjbar Noshahri F, Rostami R (2008) [Comparing family’s function of patients with substance abuse disorder and family of normal individuals]. Psychology Educational of Science . 38 (3) 137-156. (Persian) Brown BS (1998). Drug use-chronic and relapsing or a treatable condition?. Subst Use Misuse. 33 (12). 2515- 20. Chatters LM (2000). Religion and health: Public health research and practice. Annual Review of Public Health ; 21: 335-367. Chavoshi A, Talebian D, Tarkhorani H, et al (2008) [The relationship between prayers and religious orientation with mental health]. The Journal of Applied Behavioral Science . 2 (2) 156-149. (Persian) Dbbaghi P, Asgharnejad Farid AA, Atefvahid MK, Bolhari J (2007) [Effectiveness of mindfulness based-cognitive group therapy and activating spiritual schemas in preventing of relapsing use of opium]. Iranian Journal of Psychiatry and Clinical Psychology . 4 (4). 366-375. (Persian) Fathi Z, Khodabakhshi-Kolaei A, Jahantigh S, Ahmadi F (2010). The relationship between social support of family and friends on level of college students’ depression. The fifth seminar of college student’s mental health.Tehran, Iran. (Persian) Flavio FM, Kulis S, Nieri T, Parsai M (.2005). Godforbid! Substance use among religious and nonreligiousyouth. American Journal of Orthopsychiatry ; 75 (4).585-598. Fridmann P (1998). Managment of adults recovering from alcohol or other drug problems relapse prevention in primary care. Journal of The American Medical Association . 279 (15). 1227-310. Galanter M (2006). Innovations: Alcohol & drug abuse, spirituality in alcoholics anonymous. Psychiatric Services . 57 (3) .307-309. Gartner J, Larson DB, Allen GD (1991). Religious commitment and mental health: A review of the empirical literature. Journal of Psychology and Theology . 19 (1). 6-25. Janbozorgi M (1999) [The Effects of Short-term Psychotherapy (Self-Control Skills) with and without Islamic Religious Orientation on Anxiety and Stress]. Journal of Health Psychology . 2 (8) 343-368. (Persian) Kamranpoor F (2010). Level of social support, type of coping strategies and sucide in college students.The fifth seminar of college student’s mental health. Tehran, Iran. (Persian) Kearney HM (1997). Drug treatment for women traditional models and new directions Journal of Obstetric, Gynecologic & Neonatal Nursing . 26 (4). 456-68. Kodjo CM, Klein JD (2000). Prevention and Risk of Adolescent Substance Abuse. The Role of Adolescents, Families, and Communities. Pediatric Clinics of North America . 49 (2) 257-68. Meshkati MR, Meshkati Z (2002) [The Impact of Internal and External Family Factors Upon Juvenile Delinquency]. Journal of Iranian Society . 4 (3). 3-25. (Persian) Miller L, Davies M, Greenwald S (2000). Religiosity and substance use and abuse among adolescents in the National Comorbidity Survey. Journal of the American Academy of Child & Adolescent Psychiatry . 39 (9). 1190 -1197. Mokhtari A, Allahyari A, Rassolzadeh Tabatabaie K (2001). [The Relationship between Religious Orientation and Stress]. Journal of Psychology . 5 (17) 56-67. (Persian) Nonnemaker JM, McNeely CA, Blum RW (2003). Public and private domains of religiosity and adolescent health risk behaviors: Evidence from the national longitudinal study of adolescent health. Journal of Social Science & Medicine . 57 (11). 2049-2054. Nurco DN, Kinlock TW, O’Grady KE, Hanlon TE (1998). Differential Contributions of Family and Peer Factors to the Etiology of Narcotic Addiction. Drug Alcohol Depend . 51 (3). 229-237. Nurco DN, Lerner M (1996). Vulnerability to Narcotic Addiction: Family Structure and Functioning. Journal of Drug . 26 (4). 1007-1025. Pardini D, Plante T, Sherman A, Stump J (. 2000). Religious faith and spirituality in substance abuse recovery: Determining the mental health benefits. Journal of Substance Abuse Treatment . 19 (4). 347-354. Poorshahbaz A, Shamloo S, Jazayeri AR, Ghazi-Tabatabaei M (2005) [Structural relations of psychological risk and protective factors of drug abuse in adolescents]. Journal of Sociology and Social Welfare . 5 (19) 31-54. (Persian) Rahimi Movaghar A, Mohammad K, Razzaghi EM (2002). [Trend of drug abuse situation: a three-decade servey]. Hakim Journal Research . 5 (3) 171-181. (Persian) Riahi MS, Alivardi Nia A, Bani Asadi MR (2008). [The Impact of Religiosity and Religious Orientation on the Mental Health of the Students of University of Mazandaran]. Journal of social science. 5 (2) 51-90. (Persian) Robinston B, Post P (1997). Risk of Addiction to Work and Family Functioning. Psychological Reports . 81 (1) 91-95. Roghanchi M (2005). [The relationship of religious orientation with mental health of college students of Razi University]. [Dissertation]. Tehran, University of Social Walfare and Rehabilitation. (Persian) Sarvestani SR (2003). [Examining risky factors in pollution of Iranian adolescents and youngsters to substance abuse]. Journal of Social Sciences . 11 (4). 110-118. (Persian) Schaub B, Schaub R (1997). Healing Addiction (Nurse as Healer). New York: Delmar publishers. Shucksmith J, Glendinning A, Hendry L (1997). Adolescent Drinking Behavior and the Role of Family life: A Scottish Perspective. Journal of Adolescent Health . 20 (1) 85-101. Siegle, LJ, Senna JJ (, 1997). Juvenile delinquency: Theory, practice and law. Paol Alto: West. Publishing Company. نشریه دانشکده پرستاری و مامایی یونمعزردتبا. یونمعزردتبا. ی هبم ی ی یگوهمعطحجتبا / 43 ر ذ ر Sohrabi F, Najafi M (2008). Examining level of possessing of social support and mental health ofcollege students. The 4th seminar of university student’s mental health. Shiraz, Iran. (Persian) Wallace JM, Forman TA (1998). Religion’s role in promoting health and reducing risk among American youth. Journal of Health Educational Behavior . 25 (6). 721-741. Weinstein ND (1993). Testing for competing theories of health protective behavior. Journal of Health Psychology . 12 (4). 324-333. Wills TA, Yaeger AM, Sandy JM (2003). Buffering effect of religiosity for adolescent substance use. Journal of the Psychology of Addictive Behaviors . 17 (1). 24-31. Zafar Kargar Yazdi M, Kahani Sh, Bakhshi Sh, Zamani Gharrenejed Noghabi S. (2010) [Comparing coping strategies with stress, mental health, social support, probability of suicide and substance abuse in native and innative college students]. The fifth seminar of college student’s mental health. Tehran, Iran. (Persian)